Potential part of electric field of ICP coil - Azarenkov, N.A.; Gapon, A.V. (Вопросы атомной науки и техники, 2021)
ICP devices are widespread in modern technology, so the capacitive coupling in ICP is well known. It does not make a sufficient impact to the power deposition in plasma, and mostly it assumed to be a harmful effect [1]. Fortunately, making use of Faraday shield allows one to avoid a detail investigation of the capacitive coupling. However, in some cases it would be useful to account both coupling types of the inductor with a plasma [2]. There are many ways for analytical and numerical simulation of the inductors and their coupling with a plasma. In the most simulating tools, the problem comes to FEM PDE model, which includes as minima the body of an inductor wire and the surrounding space. In the paper, we use some other approach, based on integral solutions for electrodynamics potentials. Electric fields of some inductors are studied in the framework of the approach.